O Letramento Literário: As Percepções Dos Adolescentes De Uma Escola Pública Da Cidade De São Paulo - Barros, Evanise Cavalcante De [UNIFESP] (2018)
The Aim Of The Present Work Is To Access Five Adolescents" Perceptions, From Eighth Grade (Elementary School) Of A Municipal School In São Mateus, An Eastern Neighbourhood In São Paulo, Around Aspects And Circumstances Which Make Possible Practices Of Literary And Other Alternative Readings That Make Part Of Literary Reading, Identifying The Meanings Attributed To These Practices As Well As The Factors That Merge To Participate From These Practices. This Research Has As Theme Literary Literacy Through Sociohistorical And Cultural Approach Of Literacy Studies (Heath, 2004; Street, 2004, 2006, 2010, 2014; Street; Street, 2004; Barton; Hamilton, 2000; Zavala; Niño-Murcia; Ames, 2004; Gee, 2004; Kleiman, 1995, 2004; Vóvio, 2007; Aliagas Marín, 2007; Souza, 2009) And As Goal The Adolescents" Perceptions Through Merleau-Ponty"S Phenomenological Point Of View, To Whom The Perspective Experience Is Founded Over The Subject"S Embodied Experience (Nóbrega, 2008). To Access The Multiplicity Of It"S Identities Taking In